Musculoskeletal Disorders in Dental Practitioners and Ergonomic Strategies - Mahboobeh Abdolalizadeh; Fatemeh Jahanimoghadam (Negah Institute for Scientific Communication, 2015)
Introduction: In different professions, including dentistry, work-related musculoskeletal disorders (MSDs) are the main reason of loss of working period, increasing labor costs, human injuries, and absence from work. Improper posture while working is the main cause of these disorders among dentists. In this regard, identifying the risk factors and its potential harms are absolutely necessary. However, dentists are not usually informed of the role of ergonomics in the health of their musculoskeletal system. The aim of this study was to evaluate body posture in dentists' profession. Methods: Through search in PubMed, Google, Scopus, and Medline, a total of 23 original research papers were found with the keywords such as musculoskeletal disorders, dentists and ergonomics. Then, the main factors responsible for MSDs among dentists and the ways to prevent them were identified and presented. Results: Dentists working in an asymmetric and static position. Usually their head is forward and often rotates in one direction and hands are away from the body. Furthermore, dentists need eye-hand coordination to work. Maintaining this posture for a long period causes stress in the joints, muscles and tendons, especially in the neck, back, shoulder, and wrist body parts. Work equipment is not often designed ergonomically. These factors lead to musculoskeletal disorders like thoracic kyphosis, lumbar lordosis, rounded shoulders, forward head posture, supraspinatus tendinitis, and trigger points in muscles like trapezius. Conclusion: The work conditions and postures of dentists need to be improved. Furthermore, the level of dental professional education regarding the risk factors of MSDs as well as correct working conditions and postures should be increased.